Autonomy, liberalism and advance care planning - Ikonomidis, S. (Journal of medical ethics, 1999)
The justification for advance directives is grounded in the notion that they extend patient autonomy into future states of incompetency through patient participation in decision making about end-of-life care. Four objections challenge the necessity and sufficiency of individual autonomy, perceived to be a defining feature of liberal philosophical theory, as a basis of advance care planning. These objections are that the liberal concept of autonomy (i) implies a misconception of the individual self, (ii) entails the denial of values of social justice, (iii) does not account for justifiable acts of paternalism, and (iv) does not account for the importance of personal relationships in the advance care planning process. The last objection is especially pertinent in light of recent empirical research highlighting the importance of personal relationships in advance care planning. This article examines these four objections to autonomy, and the liberal theoretical framework with which it is associated, in order to re-evaluate the philosophical basis of advance care planning. We argue that liberal autonomy (i) is not a misconceived concept as critics assume, (ii) does not entail the denial of values of social justice, (iii) can account for justifiable acts of paternalism, though it (iv) is not the best account of the value of personal relationships that arise in advance care planning. In conclusion, we suggest that liberalism is a necessary component of a theoretical framework for advance care planning but that it needs to be supplemented with theories that focus explicitly on the significance of personal relationships.